Implementing Inquiry-Based Learning Strategy to Improve the Secondary Students’ Descriptive Writing Ability - Muhammad Hudri; Irwandi Irwandi (Muhammadiyah University of Mataram, 2019)
This study aims at improving the students’ writing ability in English through Inquiry-Based Learning strategy. This study employed collaborative classroom action research design in which the researchers and the collaborative teacher work together in designing the lesson plan, implementing the action, observing the action, and making reflection. The subjects of this study were the second year students of MTs. Ar Raisyiah Sekarbela of the academic year 2019/2020. This study was conducted in two cycles by following the procedure of the action research i.e. planning, implementing, observing, and reflecting. The procedures of implementing inquiry-based learning strategy in the teaching and learning writing of this study are: (1) engaging students to express their ideas in discussion activities, (2) guiding the students to investigate or observe the objects, (3) asking them to make notes of what they have investigated, (4) engaging them to make outline, (5) providing and discussing a model of text, (6) drafting rough draft based the outline, (7) revising the drafts focusing on the content and organization, (8) conducting peer editing in order to edit the grammatical aspects, (9) sharing the writing by reading it aloud in front of the class, and (10) reflecting the process of writing. The findings of the study showed that the strategy could improve the students’ ability in writing descriptive paragraphs. The improvement can be seen on the mean score of the students writing from the preliminary test, test of cycle 1 and test of cycle 2. In the preliminary, the students' mean score on the writing test was only 4.5. Meanwhile, in the test of cycle 1 was 5.9 and the test of cycle 2 became 7.1.